Development of calculation programs for batch mixtures for the production of agglomerate and pellets of a preferred chemical composition - Chuprynov , Ye.V.; Kassim , D.O.; Lyakhova , I.A.; Hryhorieva , V.G.; Rekov , Yu.V. (Theory and Practice of Metallurgy, 2025)
The article presents the results of the development and implementation of computer programs for calculating the specific consumption of charge components in order to obtain sinter and pellets of a given chemical composition. The proposed calculation system takes into account the complete chemical compositions of all charge components, the degree of solid fuel burnout, removal of calcination losses and the required basicity of the product. The programs were tested in production conditions, which showed a significant increase in the accuracy of determining the chemical composition of sinter and pellets and a reduction in discrepancies between calculated and actual data. The results obtained confirm the effectiveness of using the proposed software in the production of agglomerated blast furnace raw materials. Research objective: increasing the accuracy of the chemical composition of the resulting product by improving the program for calculating charges for the production of sinter and pellets. The subject of the study is the methodology and algorithms for determining the optimal composition of the charge for the production of sinter and pellets, based on a complete chemical analysis of the components, technological parameters of sintering and mathematical modeling of the material balance. The object of the study is the technological process of preparing and processing a charge of iron ore raw materials, including ore components, fluxes and solid fuel, in order to obtain iron ore products of a given chemical composition. Research materials: the work used chemical analyses of iron-containing materials, fluxes and solid fuel, presented in the form of complete oxide compositions. For each group of materials, weighted average chemical compositions were determined according to their specific consumption. Research results: the developed software allows you to determine the specific consumption of charge materials, taking into account their humidity and losses during technological processing. The obtained data show that the proposed program is an effective tool for stabilizing the chemical composition of sinter and pellets. Scientific novelty: a complex algorithm for calculating the charge has been developed, which simultaneously takes into account the full chemical compositions of all components (ore, fluxes, solid fuel), the degree of carbon burnout, removal of losses during calcination and various basicity options. The use of a complete chemical analysis of the charge in the calculations allows to significantly reduce the discrepancy between the calculated and actual iron content in the sinter and improve the accuracy of the blast furnace production balance. Practical significance: the developed software can be directly implemented in sinter plants and in the production of pellets, ensuring high-precision calculation of the charge in real production conditions. Reducing the discrepancies between the calculated and actual chemical composition of the sinter increases the stability of the quality of the agglomerated raw material, which has a positive effect on the operation of blast furnaces. Optimization of the specific consumption of ore components, fluxes and solid fuel allows you to reduce material overspending and ensures the rational use of resources. Conclusions. A program has been developed for calculating the specific consumption of charge components for the production of agglomerated raw materials (sinter and pellets) for blast furnace smelting, which allows you to calculate the chemical composition of the finished product from a wide range of charge components with high accuracy (viscosity less than 0.05%). The calculation is carried out with an accuracy of up to the fourth decimal place. The calculation was tested in sinter and pellet production shops and showed a significant increase in the accuracy of the chemical composition of the resulting product compared to those used at enterprises.